The Application of International Product Advertisements as Intercultural Learning Media - Maria Ulfa; Sri Handayani (Hasanuddin University, 2025)
Language acquisition inherently requires intercultural competence, yet understanding implicit foreign cultural nuances remains a challenge for learners. This study aims to describe the application of international product advertisements as intercultural learning media and to analyze students' understanding and responses regarding their utilization. The research employed a quantitative descriptive method with a pre-experimental One-Shot Case Study design. The participants were 31 fourth-semester students of the French Language Education Study Program. The treatment involved analyzing Toyota advertisements adapted for Indonesia and France to examine cultural contrasts within the 'savoirs' framework. Data were collected using knowledge tests and response questionnaires. The results demonstrated that the application of international product advertisements was highly effective. Cognitively, students achieved a satisfactory mean score of 80.26, attaining 100% classical mastery based on standard criteria. Students successfully identified that the Indonesian advertisement reflected broad social realities and collectivism, while the French advertisement emphasized national identity and individualism. Affectively, the media received a positive reception, with 80.6% of students responding